TNF inhibitors target a mevalonate metabolite/TRPM2/calcium signaling axis in neutrophils to dampen vasculitis in Behçet’s disease - Menghao Zhang; Na Kang; Xin Yu; Xiaoyang Zhang; Qinghui Duan; Xianqiang Ma; Qiancheng Zhao; Zhimian Wang; Xiao’ou Wang; Yeling Liu; Yuxiao Zhang; Can Zhu; et al. (Nature Communications)
Abstract TNF inhibitors have been used to treat autoimmune and autoinflammatory diseases. Here we report an unexpected mechanism underlying the therapeutic effects of TNF inhibitors in Behçet’s disease (BD), an autoimmune inflammatory disorder. Using serum metabolomics and peripheral immunocyte transcriptomics, we find that polymorphonuclear neutrophil (PMN) from patients with BD (BD-PMN) has dysregulated mevalonate pathway and subsequently increased farnesyl pyrophosphate (FPP) levels. Mechanistically, FPP induces TRPM2-calcium signaling for neutrophil extracellular trap (NET) and proinflammatory cytokine productions, leading to vascular endothelial inflammation and damage. TNF, but not IL-1β, IL-6, IL-18, or IFN-γ, upregulates TRPM2 expression on BD-PMN, while TNF inhibitors have opposite effects. Results from mice with PMN-specific FPP synthetase or TRPM2 deficiency show reduced experimental vasculitis. Meanwhile, analyses of public datasets correlate increased TRPM2 expressions with the clinical benefits of TNF inhibitors. Our results thus implicate FPP-TRPM2-TNF/NETs feedback loops for inflammation aggravation, and novel insights for TNF inhibitor therapies on BD.